(untitled) (Web of Teachers: Inderscience Research, 2023)
Empathy, theoretical aspect of empaty, psychological features of pedagogical empathy in students are are explained in this article. Pedagogical empathy is not formed in the personality of students, and it is specific according to age periods and course stages. Emotional identification in 18-19-year-old students; 20-21 year old students; have seriousness with emotionality; identification, intuitivenness in 22-23 year old students, it was found that emo-emotion coordination and identification, rationality, identification, pedagogical empathy